Efficacy and safety of CO2 insufflation during colonoscopy. Clinical trial - Osvaldo Raiko Seijas Cabrera; Enrique Olazábal García; Maricela Morera Pérez; Frank Pérez Triana; Elizabeth Montes de Oca Mejías; Jorge Luis García-Menocal Hernández (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Colonoscopy is the technique of choice for the study of colon's disease and in certain pathologies a therapeutic option. Colon insufflation normally performed using ambient air which led this technique to be painful. Insufflation with carbon dioxide (CO2) causes less abdominal pain. Objective: To evaluate, the efficacy and safety of CO2 insufflation during colonoscopy. Material and Methods: A double-blind randomized controlled trial (Phase IIb) was performed. Universe: all patients with indication of colonoscopies that met the selection criteria and assist to the Minimal Access Surgery National Centre in Havana in the period from October to December 2014. The sample consisted of a total of 100 patients over 18 years of which 50 were subject to the air insufflation technique and 50 with CO2 insufflation. Results: Abdominal pain after colonoscopy was significantly lower in the group that received the CO2 insufflation. Hypoxemia and propofol doses used were similar in both groups. CO2 average pressure values were higher in the case of the CO2 group during the procedure but within the normal range; without clinical complications. Conclusions: The use of CO2 in colonoscopy causes significantly less pain in the first hour. Its use in patients with deep sedation is safe and the technique is not altered and doesn't have a time reduction.  Keywords: Colonoscopy, carbon dioxide, efficacy, safety, clinic trial, abdominal pain, hypoxemia, sedation.